Local Climatic Factors Mediated Impacts of Large-Scale Climate Oscillations on the Growth of Vegetation Across the Tibetan Plateau - Zhang, Lei; Shen, Miaogen; Shi, Chunming; Shi, Fangzhong; Jiang, Nan; Yang, Zhiyong; Ji, Zhenming (Frontiers in Environmental Science, 2021)
Large-scale climate oscillations, particularly the Atlantic Multidecadal Oscillation (AMO) and the Pacific Decadal Oscillation (PDO), have widespread influences on climate systems across the Tibetan Plateau (TP). It is understudied how the temporal changes in AMO and PDO affected growth of vegetation through modifying the local climatic factors in different areas across the TP. We used the AMO and PDO indices, gridded growing season mean temperature (TGS), cumulative precipitation (PGS), and normalized difference vegetation index (NDVIGS) data from 1982 to 2015 to investigate the temporal trends of these variables and the correlations of the TGS and PGS with each of the AMO and PDO indices as well as their correlations with the NDVIGS. The results showed that the warming of the TGS over the TP and the increases of the PGS in western, central, and northeastern areas of the TP may have been related to an increase of the AMO index and a decrease of the PDO index. Combining those relationships with the spatial patterns of the TGS-NDVIGS and PGS-NDVIGS correlations suggested that the changes of the AMO and PDO may have indirectly increased the NDVIGS in the central and northeastern areas of the TP by increasing TGS and PGS, in most parts of the southwestern TP by increasing PGS, and in the eastern and south-central regions of the TP by increasing TGS. In contrast, the decrease of the NDVIGS in some areas of the southeastern and southwestern TP may have been associated with a negative effect of warming as a result of changes in the AMO and PDO. These results highlight the indirect impacts of changes in large-scale climate oscillations on the growth of vegetation through modification of local climatic factors across the TP, and they suggest the substantial spatial heterogeneity of these impacts largely depends on the responses of vegetation to local climatic factors.